Analisis Pola Ejaan Dalam Teks Pidato Mahasiswa - Wa Ode Irawati (ARDHI : Jurnal Pengabdian Dalam Negri, 2023)
This study aims to analyze spelling patterns in the form of spelling errors in student speech texts. This research uses descriptive qualitative research. The source of data in this research is the speech texts of students of the Department of Indonesian Language and Literature Education Semester 5, Faculty of Letters and Culture, Gorontalo State University in the 2022/2023 academic year. The data in this study are sentences that contain spelling mistakes in accordance with EYD in the form of letter usage, word writing, punctuation usage, and writing of absorbed elements. The number of speech texts in the research is 40 speech texts. The data collection techniques used in this research are documentation, reading technique, and note-taking technique. The data analysis technique in this research goes through several stages, namely data reduction, data presentation, data inference and verification, and final conclusion. The results of this study show that there are three forms of spelling errors in speech texts written by students, namely the use of letters, word writing, and the use of punctuation marks. The errors in the use of letters include errors in the use of capital letters as many as 20 errors consisting of errors in writing titles, geographic names, and greetings. Meanwhile, there were 5 italicization errors consisting of foreign language writing errors. Word writing errors in the form of preposition writing errors consist of 10 errors. Punctuation errors include 5 period errors and 27 comma errors.